Nerve regeneration through a healthy nerve trunk: A new and hopeful conduit for bridging nerve defects - ERCAN, FERİHA (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Background: Considering a healthy nerve trunk as the hypothetically ideal conduit, a new experimental model using an intact nerve for bridging a nerve defect was contemplated. Methods: Thirty rats Were used. In group I (double coaptation), a segment was removed from the peroneal nerve. Both the proximal and distal stumps were repaired end-to-side to the tibial nerve. In group II (only distal coaptation), only the distal nerve stump was repaired. In group III (control), the transected segment was immediately repaired primarily in its original orientation as a nerve graft. A walking track analysis was conducted periodically for 28 months. The horseradish peroxidase retrograde labeling technique was used for tracking the origin of the axons presented in the distal stump of the peroneal nerve in group I, and morphologic studies were also carried out for all the groups. Results: Functional assessment revealed that the difference between group I and group II was significant. The horseradish peroxidase labeling test suggested that the nerve fibers in the distal stump of the peroneal nerve were mostly from its original proximal stump passed by the way of the tibial nerve bridge. Conclusion: This study suggested that the axons of the proximal stump of a sectioned nerve can sprout into another intact nerve trunk by the way of an end-to-side repair site, regenerate, and advance in its epineurium distally for a distance and pass into Its original distal Stump if it was repaired end-to-side. It was thought that the technique could be used in clinical cases with short nerve defects as an alternative method to grafts and conduits.
Keywords: TO-SIDE NEURORRHAPHY; POLYGLYCOLIC ACID CONDUITS; VEIN GRAFT REPAIR; RAT MODEL; SKELETAL-MUSCLE; INTACT NERVE; RECONSTRUCTION; SURGERY